Difference spectrum fitting of the ion-neutral collision frequency from dual-frequency EISCAT measurements - Günzkofer, Florian Ludwig; Stober, Gunter; Pokhotelov, Dimitry; Miyoshi, Yasunobu; Borries, Claudia (Atmospheric Measurement Techniques, 2023)
The plasma-neutral coupling in the mesosphere-lower thermosphere strongly depends on the ion-neutral collision frequency across that region. Most commonly, the collision frequency profile is calculated from the climatologies of atmospheric models. However, previous measurements indicated that the collision frequency can deviate notably from the climatological average. Direct measurement of the ion-neutral collision frequency with multifrequency incoherent scatter radar (ISR) measurements has been discussed before, though actual measurements have been rare. The previously applied multifrequency analysis method requires a special simultaneous fit of the two incoherent scatter spectra, which is not possible with standard ISR analysis software. The difference spectrum method allows us to infer ion-neutral collision frequency profiles from multifrequency ISR measurements based on standard incoherent scatter analysis software, such as the Grand Unified Incoherent Scatter Design and Analysis Package (GUISDAP) software. In this work, we present the first results by applying the difference spectrum method. Ion-neutral collision frequency profiles obtained from several multifrequency EISCAT ISR campaigns are presented. The profiles obtained with the difference spectrum method are compared to previous collision frequency measurements, both from multifrequency ISR and other measurements, as well as results from empirical and comprehensive atmosphere models. Ion-neutral collision frequency measurements can be applied to improve first-principle ionospheric models